Odontometric Analysis of Permanent Mandibular Canine to Determine Sexual Dimorphism: A Preliminary Study - Bajracharya, Mangesh; Omar, B.K.; Maharjan, S.K. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: Crown diameters of a teeth are reasonably accurate predictors of sex and are good adjuncts for sex determinations. The aim of the study was to determine the reliability of mesiodistal width of mandibular canine in sexual dimorphism. Materials and methods: Medical students of Nepalgunj Medical College, Chisapani, Banke, Nepal were selected for data collection. Sample consisted of 300 subjects which included 150 males and 150 females of age group 18-25 years. The mesiodistal width of the mandibular right and left canine teeth were recorded by Vernier calliper. Descriptive statistical analysis was done from odontometric measurements data to calculate sexual dimorphism for mandibular right and left canine. The student t-test was used to determine the level of significance among the parameters measured. Results: The mean values for mesiodistal width of mandibular right canine for male and female subjects were 7.1665±0.28576 and 6.3777±0.37875 respectively. The sexual dimorphism for mandibular right canine was calculated to be 12.368%. The mean values for mesiodistal width of mandibular left canine for male and female subjects were 7.3875±0.35506 and 6.2847±0.41115 respectively. The sexual dimorphism for mandibular left canine was calculated to be 17.5%. Conclusion: Statistical analysis showed significant sexual dimorphism in odontometric analysis of permanent mandibular canines between male and female with the mandibular left canine showing the highest percentage.